ANALISIS YURIDIS PROSEDUR PENDIRIAN CV SEBAGAI BENTUK PERLINDUNGAN HUKUM UMKM DI JAKARTA - Khairan, Gyas; Pradnya Ubaedi, Jazlynne Attia; Ar Rabbani, Muhammad Mirza (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
Although the establishment of a Commanditaire Vennootschap (CV) is officially regulated and facilitated through the Online Single Submission (OSS) system, many micro, small, and medium enterprises (MSMEs) in Jakarta continue to face obstacles. These challenges include limited understanding of legal procedures, high notary fees, and bureaucratic inefficiencies. Despite these issues, registering a CV offers clear benefits such as improved access to funding, legal clarity, and separation between personal and business assets, which contributes to business resilience. This study adopts a qualitative empirical legal approach using descriptive-analytical methods. Data were collected through reviews of legal documents, academic sources, and interviews with MSME owners and legal officials. The research aims to analyze the legal framework, practical challenges, and advantages of CV registration as a form of legal protection for MSMEs in Jakarta. The study concludes that effective legal protection requires more than just clear regulations—it also depends on supportive policies, legal education, and hands-on assistance from local authorities.Keywords : Business legality, Legal protection, Micro enterprises, OSS system, Partnership